Post-offence explanations of exhibitionists - Thomas, Mackenzie (My University, 2022)
There is little research exploring post-offence explanations and acceptance of responsibility among individuals who engage in exhibitionism. Despite research suggesting that denial is not associated with recidivism, when sexual offenders attribute their criminal behaviour to multiple internal and external factors, their explanations are often deemed problematic, seen as a responsivity factor, and consequently, lead to exclusion from treatment (Yates, 2009; Maruna & Mann, 2006). We sought to investigate explanations given by individuals who have been convicted of sexual offences involving exhibitionistic acts and compare the cognitive distortions of those with prior sexual offences (contact or non-contact) versus those without. The files of 40 offenders were coded to create a descriptive record of the offenders’ behavioural characteristics and different types of explanations given after committing their crimes. With 15% demonstrating categorical denial, the majority of the sample acknowledged the charges for an indecent act, thereby giving explanations that minimized the offence rather than absolute admittance of criminal motives. Not surprisingly, we found significant differences in offender behaviour and criminal sentencing, with individuals who had prior sexual offences reporting a higher sex drive and receiving longer conditional sentences. In terms of explanations used by offenders, individuals with a history of prior sexual offences were significantly less likely to exhibit complete denial and more likely to explain that their exhibitionistic behaviours were motivated by sexual arousal or resulted from internal character. This study provides an empirical examination of explanations used by individuals who engage in exhibitionistic behaviour. Furthermore, it has implications for practitioners to better engage these offenders in treatment and, therefore, address responsivity issues that may emerge.
Presented on February 4, 2022 at the 2nd Annual Canadian Forensic Psychology Virtual Conference at Saint Mary's University in Halifax, Nova Scotia.
Keywords: exhibitionism; cognitive psychology; sex offenders; criminal behavior, prediction of